Microwave Treatment on Two Fast Growing Trees Species for Bioethanol Production - Lucky Risanto; Euis Hermiati; Danang S Adi (Masyarakat Peneliti Kayu Indonesia, 2012)
The objectives of this research were to analyze chemical component and to evaluate the effect of micro wave treatment on the bioethanol production of “balik angin daun kecil” and “balik angin daun sedang” woods. Woods were milled to the size of 40-60 mesh and followed by measuring their chemical component. Glycerol and 0.5% sulphuric acid were added to the woods with the ratio of 10:1 and 20:1, respectively and then irradiated to the micro waves for 2.5-10 min. with power 50 and 70%. The pulp was hydrolyzed with cellulose for 48 H and reducing sugar yield was obtained. The results indicated that hollocellulose and alpha cellulose of “balik angin daun kecil” wood was higher than that of “balik angin daun sedang” wood. Conversely, lignin content of “balik angin daun kecil” wood was lower than that of “balik angin daun sedang” wood. The highest reducing sugar yield of balik angin daun kecil and balik angin daun sedang woods were 21.00% and 22.40%, respectively and they were obtained on irradiated to microwaves for 5 min at 70% power.Key words: balik angin, bioethanol, chemical component, enzymatic hydrolysis, microwave